Development of an HIV Postexposure Prophylaxis (PEP) Protocol for Trainees Engaging in Academic Global Health Experiences. (November 2017) - Arora, Gitanjli; Hoffman, Risa M.
Abstract : Problem: Global health (GH) education programs have become increasingly common in U.S. medical schools and graduate medical education programs, with growing numbers of medical students, residents, and fellows participating in clinical experiences in settings with high HIV prevalence and limited resources. However, there are no guidelines for provision of HIV postexposure prophylaxis (PEP) to trainees engaging in these academic GH experiences. Approach: Faculty of the Global Health Education Programs (GHEP) at the David Geffen School of Medicine at UCLA and GH partner institutions recognized the need for PEP access for trainees engaged in GH experiences. In 2013–2014, key UCLA faculty collaborated in the development of the UCLA GHEP PEP Protocol, which includes provision of PEP medications to trainees prior to departure, an on-call infectious disease/HIV specialist to advise trainees who have exposures, and a system for following up with exposed trainees while on the GH rotation and after their return. Outcomes: Between February 2014 and September 2016, 112 medical students and 110 residents received education on the PEP protocol during their predeparture orientation. The protocol was used for 28 exposures (27 occupational, 1 nonoccupational), with PEP recommended in 3 occupational cases (all needlesticks) and the single nonoccupational case. There were no reported HIV seroconversions. Next Steps: The authors plan to formally evaluate the PEP protocol, conduct a qualitative assessment with trainees and both UCLA and GH partner faculty, and discuss best practices with institutions across the United States and with GH partners. Abstract : Supplemental Digital Content is available in the text.